Kompetensi dan Independensi Auditor Pengaruhnya pada Kualitas Audit - Castellani, Justinia (Jurnal Trikonomika, 2008)
This research purpose to prove the hypotesis that auditorâs competence and independence influence the quality audit. This descriptive and verifikatif research give description above variables which investigated, involved 51 auditors that working settled in Public Accountant Firm in Bandung, in May 2007 and have three years minimum experience, as respondents. Using likert scale as an instrument for measure auditorâs perceptions about the competence and independence that influence audit quality. Hypothesis analysis method was tested used path analysis. The result of the analysis, showed empirical testimony that auditorâs competence and independence significantly influence audit quality, according to auditorâs perceptions. The independence extended more dominant influence (49%) than competence (28%), while the rest (23%) decided by another factor that doesnât detect in this research. Auditor with good knowledge, experience and follow technical training having ability more good to find insincerity or mistake in client financial statement, so that can yield qualified audited process and financial report.